Kletvata vo makedonskata tradicionalna kultura - Petreska, Vesna (Wydawnictwo Naukowe UAM, 2012)
Curses are spoken formulas that express a desire to happen something bad in the future to someone or something, with the assurance that it will capture. This conviction or belief is based on faith in the magical power of the word. In the folk life curses are being made when the most important values in the community are injured. Therefore, curses are discussed in relation to the values that are maintained in a given community, and their violation determines sin, and depending on the committed sin and weights required curses or punishments. Looking from this social perspective, they represent a measure of values in the society that occurres as an indication of distortion of values, whether those who suggest deteriorated values occupy a high or low social status in the community or family. The curse is correcting the distortion, i.e. some satisfying justice, out exclusively on force majeure, and indefinitely. In this regard it emphasizes that the most important values in traditional Macedonian culture were life itself, created progeny, and their family, property and honor. Most evidence of the belief in the power of the curse by folk stories is the event of an accident either cursed person or his family. Therefore, curses also point another very important value, which is highly appreciated – the natural course of human life, birth-marriage-death, that value in ritual practices tend to emphasize or re-establish if it is disturbed, and curses she tries to unravel.
Curse in Macedonian Traditional Culture
Keywords: Curse; Sin; Values; Macedonian folk culture; Punishment